Biochar facilitates rapid restoration of methanogenesis by enhancing direct interspecies electron transfer after high organic loading shock. (January 2021) - Wang, Chen; Liu, Yang; Wang, Caiqin; Xing, Bo; Zhu, Shaodong; Huang, Jinjing; Xu, Xiangyang; Zhu, Liang
Highlights: Biochar promoted rapid restoration of methane production after organic loading shock. Biochar maintained structural stability of granular sludge under the stress of VFAs. The enrichment of DIET-partners enhanced balance of acidogenesis and methanogenesis. Biochar retained Methanosaeta and Methanosarcina under the stress of VFAs. Abstract: This study evaluated the effectiveness of biochar addition against high organic loading shock (OLS) of 80 kg COD/m 3 /d in up-flow anaerobic sludge blanket (UASB) reactors (R1 with biochar; R2 without biochar). After OLS of 24 h, R2 suffered the irreversible acidification (pH of 5.42 ± 0.07) with low biogas production of 0.08 ± 0.01 m 3 /kg COD/d. In contrast, the biogas production in R1 restored rapidly to 0.33 ± 0.04 m 3 /kg COD/d, and effluent pH in R1 returned to 7.01 ± 0.22. With addition of biochar, potential direct interspecies electron transfer (DIET) partners, including volatile fatty acids (VFAs)-oxidizing bacteria ( Bacteroidetes, Smithella, Desulfovibrio, Geobacter ) and methanogens ( Methanosaeta, Methanosarcina ) were enriched in R1, which were conductive to maintain the balance of acidogenesis and methanogenesis. Moreover, the retention of Methanosaeta and Methanosarcina coupled with biochar maintained the structural stability of granular sludge in R1 under the pressure of OLS and VFAs, which guaranteed the stability of anaerobic system.